A randomized double‐blind crossover study of indoor air filtration and acute changes in cardiorespiratory health in a First Nations community. (19th January 2013) - Weichenthal, S.; Mallach, G.; Kulka, R.; Black, A.; Wheeler, A.; You, H.; St‐Jean, M.; Kwiatkowski, R.; Sharp, D.
Abstract Few studies have examined indoor air quality in First Nations communities and its impact on cardiorespiratory health. To address this need, we conducted a crossover study on a First Nations reserve in Manitoba, Canada, including 37 residents in 20 homes. Each home received an electrostatic air filter and a placebo filter for 1 week in random order, and lung function, blood pressure, and endothelial function measures were collected at the beginning and end of each week. Indoor air pollutants were monitored throughout the study period. Indoor PM2.5 decreased substantially during air filter weeks relative to placebo (mean difference: 37 μg/m3, 95% CI: 10, 64) but remained approximately five times greater than outdoor concentrations owing to a high prevalence of indoor smoking. On average, air filter use was associated with a 217‐ml (95% CI: 23, 410) increase in forced expiratory volume in 1 s, a 7.9‐mm Hg (95% CI: −17, 0.82) decrease in systolic blood pressure, and a 4.5‐mm Hg (95% CI: −11, 2.4) decrease in diastolic blood pressure. Consistent inverse associations were also observed between indoor PM2.5 and lung function. In general, our findings suggest that reducing indoor PM2.5 may contribute to improved lung function in First Nations communities.